Urgent need to strengthen school health in Asia and the Pacific islands. Issue 12 (28th October 2021) - Kobayashi, Jun; Takeuchi, Rie; Toyama, Yuko; Gregorio, Ernesto R.; Kadriyan, Hamsu; Estrada, Crystal Amiel M.; Motomura, Makoto; Wake, Norie; Yamada, Kyoko; Ishikawa, Ryuji; Takakura, Minoru
Abstract: In Asia and the Pacific island region, strengthening of school health activities and measures is urgently recommended to deal with the impact of the increasing risk of potential school closures due to continuation of the coronavirus disease 2019 (COVID‐19) pandemic in 2021. As the incidence of COVID‐19 in 2020 was relatively low in these regions, many of the countries were able to avoid prolonged school closures. However, even if vaccination is expanded in the future and the pandemic tends to come to an end, the risk of SARS‐CoV‐2 variants spreading among children will also increase, and the possibility of having to close schools again will also increase.